2004
DOI: 10.1002/cbic.200300655
|View full text |Cite
|
Sign up to set email alerts
|

Loading of the Antigen‐Presenting Protein CD1d with Synthetic Glycolipids

Abstract: CD1 proteins present mammalian and microbial lipid and glycolipid antigens to different subsets of T cells. Few such antigens have been identified and the binding of these to CD1 molecules has mainly been studied by using responding T cells in cellular assays or recombinant solid-phase CD1 proteins. In the present study we use four different glycolipids, some of which contain tumor-associated carbohydrate antigens, to develop a procedure to easily detect binding of glycolipids to CD1 proteins on viable cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…However, only a fraction of NKT cells detected by agalactosylceramide (a-GalCer) could be stained by a CD1d tetramer loaded with mycobacterial PIM [6]. A recent study [7] was able to show the binding of synthetic a-GalNAc containing GSL to cell surface CD1d, but no functional studies were done to demonstrate the T cell relevance of this antigen. To date, aGalCer -originally isolated from marine sponges [8] -is the only available ligand for phenotypically and functionally characterizing NKT cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a fraction of NKT cells detected by agalactosylceramide (a-GalCer) could be stained by a CD1d tetramer loaded with mycobacterial PIM [6]. A recent study [7] was able to show the binding of synthetic a-GalNAc containing GSL to cell surface CD1d, but no functional studies were done to demonstrate the T cell relevance of this antigen. To date, aGalCer -originally isolated from marine sponges [8] -is the only available ligand for phenotypically and functionally characterizing NKT cells.…”
Section: Introductionmentioning
confidence: 99%
“…To explore the mechanistic and kinetic details of ligand association with CD1d molecules, a more direct method of detecting α-GalCer:CD1d complexes would be of great value. The straightforward technique of using fluorescent, radio-or biotin-labeled α-GalCer molecules as probes for complex formation is hampered by the problem that these probes can associate with the cell surface independently of CD1d, probably through nonspecific interactions with membranes and hydrophobic protein domains (Wallner et al, 2004; data not shown).…”
Section: Introductionmentioning
confidence: 99%
“…One is to depend on high-throughput screening of a huge number of drug candidates produced by combinatorial chemistry. 49 However, both RCAI-5 and RCAI-6 were almost inactive. The other is to design candidate compounds by so-called "structure-based design" using the structural information obtained by X-ray crystallographic analysis of a lead compound and its receptor protein.…”
Section: Analogs Of Krn7000 Prepared In 2003-2006mentioning
confidence: 98%